Improving speaking skills in early childhood through the song “I am a Muslim”: An experimental study - Erlangga, Rifqi Aulia; Syukur, Abdul (Universitas Sarjanawiyata Tamansiswa, 2022)
Early childhood education is crucial for both religion and English learning. Previous studies have shown that social media is helping today's youth learn more about religion and English. This study aimed to analyze the effectiveness of teaching religion and English with song media in early childhood through an experimental study of the song I am I a Muslim by Yusuf Islam. This study's theoretical contribution can help develop the theory of religion and English education for early childhood and be practically valuable for teachers or parents. This study was an experimental study. A sample of 32 children (4-12 years) was qualitatively analyzed. The results revealed that the respondents' habit of listening to the song I Am A Muslim grew over time. The aspects not confirmed by this study's findings included the mood factor of the children so the facilitators, the environment in which children study, and the type of children's learning style, despite the fact that the hypotheses postulated in this study had not been proved 100%. This study has demonstrated that most respondents experience an improvement in English language abilities and Islamic knowledge via song since there are still some limitations to this study. The future study can include using control elements that impact learning success and doing research in the same areas.